Influence of Conflict Management strategies on Performance of National Registration Bureau in Busia County - Obwaku, Christine Iyaya (JOOUST, 2018)
Conflict becomes a problem when it lowers morale, causes more conflicts and causes inappropriate behaviors, which ultimately affects performance. Over 35.4% of 183 employees in national registration bureaus in Busia County participated in different kinds of conflicts between 2008 and 2012. This incorporated those who forcefully resisted transfers, those who fought amongst themselves and those who engaged in office politics. It is because of this that the study was set to determine the influence of conflict management strategies on performance in national registration bureaus in Busia County. The specific objectives were to: determine the influence of avoidance strategy on performance; assess the influence of collaboration strategy on performance; establish the influence of accommodation strategy on performance; determine the influence of competition strategy on performance; and establish the influence of compromise strategy on performance in national registration bureaus in Busia County. The study was guided by contingency theory of management and conducted through cross sectional survey research design. The target population was 183 employees from 10 national registration bureaus in the county. A sample size of 132 employees was arrived at through Krejcie and Morgan tables of samples and selected through stratified sampling technique. Data collected through questionnaires was analyzed descriptively and results presented in tables. Despite the high usage of avoidance strategy (M=4.80; SD=. I 0) performance measures: effectiveness (M= 1.72; SD= .13); efficiency (M=2. I 6; SD=.51); and quality service delivery (M=2.28; SD=.29) consistently showed low results. The high usage of collaboration strategy (M=4.26; SD=.21) was consistent with high performance measures: effectiveness (M=4.60; SD= .26); efficiency (M=3.35; SD=.84); and quality service delivery (M=3.70; SD=.85). The high usage of accommodation strategy (M=4.36; SD=.62) was also consistent with high performance measures: effectiveness (M=4.33; SD=.36); efficiency (M=3.35; SD=.82); and quality service delivery (M=3.64; SD=.82). Despite intense usage of competition strategy (M=4.36; SD=.62) performance measures: effectiveness (M=l .57; SD=.26); efficiency (M=2.05; SD=.50); and quality service delivery (M=l .92; SD=.44) showed consistently low results. Also, despite the high usage of compromise strategy (M=4.16; SD=.83) performance measures: effectiveness (M=l .92; SD=.47); efficiency (M= 1.91; SD=.50); and quality service delivery (M=2.24; SD=.74) showed consistently low results. In conclusion, accommodation and collaboration were the most instrumental conflict management strategies in improving performance at the national registration bureaus in Busia County. The results will contribute to the existing body of knowledge in conflict management, help the government of Kenya identify appropriate strategies in managing conflict for improved performance and formulate policies on conflict management strategies in national registration bureaus. The study therefore recommends that the department of national registration bureau should: develop a manual for identification of conflicts and appropriate management techniques; and conduct research to validate the viability conflict management strategies to use in their management programs.